Regulation factors of denitrification and their influence on emissions of N2O from pasture soil - Brůček, Petr (Jihočeská univerzita, 2010)
Regulating factors of denitrification and their effect on emissions of N2O from pasture soils in a cattle overwintering area were investigated. The study was based on field experiments performed at three locations along the gradient of animal impact and on laboratory experiments focused on effect of nutrients addition on N2O emissions.
Regulation factors of denitrification and their influence on emissions of N2O from pasture soil
Keywords: dusík v půdě; emise N2O; denitrifikace; soil nitrogen; N2O emissions; denitrification